RANCANG BANGUN SISTEM KONTROL TEKNIK PENYIRAMAN TANAMAN HIDROPONIK BERBASIS ARDUINO - Chairil Ardin, Andra Pratama Karsal, Tan Suryani Sollu, Maryantho Masarrang (Foristek, 2018)
Hydroponics is a planting technology that utilizes water without using soil as a growing medium by emphasizing the fulfillment of nutritional needs for plants, the temperature of plant nutrients and watering techniques used. This research aims to design a system to control NFT (Nutrient Film Technique), DFT (Deep Flow Technique) and Ebb and Flow techniques and control the temperature of nutrients water and monitor nutritional water requirements. The result of the research shows that the design of hydroponic plant watering system has been developed. In the Ebb and Flow hydroponics system the process of administering the nutrient solution using a timer while the water temperature of the nutrients is kept optimum 18oC to 28oC using DS18B20 temperature sensor and chiller. While monitoring water level nutrition using water level sensors and GSM module. The GSM module sends a message when the water level of the nutrient reaches a certain level in the reservoir and the alarm will give notice of buzzer when the nutrient water is at low level.